Pengaruh Kemampuan Teknik Personal dan Keterlibatan Pemakai pada Efektivitas Penggunaan SIA dengan Pelatihan sebagai Variabel Pemoderasi - Indrianto, Ivana Elvaretta; Dharma Suputra, I Dewa Gede (E-Jurnal Akuntansi, 2020)
This study was conducted to obtain empirical evidence about the influence of personal technical ability and user involvement on the effectiveness of using SIA with training as a moderator at the KSU in West Denpasar City. This research was conducted at 24 KSU in West Denpasar City. The sample of this study were 72 respondents with a purposive sampling method. Data collection is done by distributing questionnaires. The analysis technique used is multiple linear regression. The results of this study indicate that the ability of personal techniques has a significant positive effect on the effectiveness of the use of SIA. User involvement significantly positive effect on the effectiveness of the use of SIA. Training strengthens the influence of personal technical abilities and user involvement on the effective use of SIA. Keywords: Personal Technical Ability; User Involvement; Effectiveness of SIA Use.